Metabolomics combined with molecular docking and dynamics simulation to investigate the mechanism of action of Fibraurea recisa Pierre in the treatment of chronic urticaria - Xiao, Tian; Tao, Jie; Tan, Jiaoyang; Zhao, Zhourong; Yang, Liping; Zhang, Chao; Duan, Xiaohua (Frontiers in Pharmacology, 2025)
BackgroundThis study investigated the mechanism of action of Fibraurea recisa Pierre (FRP) in the treatment of chronic urticaria (CU) using a rat model and combinatorial analysis of network pharmacology, metabolomics, and molecular dynamics and dynamics simulation data, providing a rationale for its clinical use.MethodsTwenty-four Sprague-Dawley rats were categorized into control, model, high-dose FRP (40 mg/kg body weight), and low-dose FRP (20 mg/kg body weight) groups. The CU model was induced by ovalbumin. Ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC/MS) was used to estimate the levels of various components in FRP. The rats in different groups were evaluated for scratching behavior, histopathological changes in the skin tissues based on hematoxylin/eosin staining, and the levels of inflammatory factors and indicators of mast cell degranulation. Metabolomics, network pharmacology, molecular docking and dynamics simulation, and Western blotting were used to analyze the mechanism of action of FRP.ResultsWe identified 2,206 compounds in FRP based on UPLC/MS data analysis. Our data showed that the main active components in FRP were palmatine, jatrorrhizine, and coclaurine. FRP administration significantly reduced the scratching frequency, pathological characteristics of skin tissues, levels of inflammatory factors, and the degree of mast cell degranulation. Based on the combined analysis of metabolomics and network pharmacology data, phosphatidylinositol 3-kinase (PI3K)-protein kinase B (Akt) signaling pathway was identified as the key target of FRP. Molecular docking and molecular dynamics simulation demonstrated strong and stable binding of Akt with palmatine, jatrorrhizine, and coclaurine. Western blotting confirmed that FRP increased the levels of p-Akt and p-PI3K in skin tissue within the CU model.ConclusionFRP significantly alleviated the symptoms and pathological changes of CU by modulating inflammation through upregulation of the PI3K-Akt signaling pathway.